Strategic evolution of the armed conflict in colombia (2009)
This article proposes an interpretation of the armed conflict from an evolutionary view that takes into account the concept of private protection agencies in the works of Schelling / Nozick / Gambetta. Its aim is also to assess the dynamics of conflict and changes from the author’s scientific output. A context of conflicts that includes new expressions of violence and the relative failure of the paramilitary reintegration involves using new analytical models (argumentation, game theory and inconsistent information). The recent evolution of emerging bands and their expansion into areas that were paramilitary camps requires monitoring not only by the government and authorities, but also from those researching the conflict in its current phase. The author proposes a heuristic research support from Schelling’s theory of strategy, Nozick’s protection agencies, and Gambetta’s recent contributions on the relationshi p between organized crime and drug cartels.